Testing the Null Hypothesis of Stationarity of Internet Traffic - Lauks, G.; Skrastins, A.; Jelinskis, J. (Elektronika ir Elektrotechnika, 2011)
The statistical analyses indicate that the measured traffic traces from the packet networks often contain non-stationary effects. In these cases several popular tests for long-range dependence and/or stationarity can result in wrong conclusions and unreliable estimate of the Hurst parameter. In this paper non-stationarities are modeled as the trends and/or level shifts in Internet traffic data. MMPP-Based Hierarchical Model simulation data are used for stationarity tests. Application of testing results are integrated into network resource allocation function as a Partially Observable Markov Decision process. Ill. 4, bibl. 7, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.112.6.439